Correlation between morphological properties and ionic conductivity in an electrolyte based on poly(vinylidene fluoride) and poly (2-hydroxyethyl methacrylate) - J. S.,Lívio Bruno (2014)
Materials based on a mixture of poly(vinylidene fluoride) (PVDF), poly(2-hydroxyethyl methacrylate) (PHEMA) and LiClO4 were produced to evaluate their ionic behavior and morphological structure to determine if they can be used as an electrolyte in electrical devices. FTIR chemical analysis results indicated the presence of interactions between PVDF, PHEMA and LiClO4. MDSC results showed that the transition temperatures of the polymers shifted to higher temperatures for systems containing high concentrations of each polymer. SEM images indicated that there was some miscibility between the polymers especially for the 25 and 75 wt. % compositions. In terms of the electrical performance, the ionic conductivity level of the electrolyte could be controlled by changing the composition of the system.